Buddha in the marketplace : the commodification of Buddhist objects in Tibet - Catanese, Alex John (Traditions and transformations in Tibetan Buddhism, 2019)
"This book explores a controversial issue within the Tibetan Buddhist tradition: The selling and profiting from the sale of Tibetan Buddhist religious objects among Tibetans. The book combines textual and historical research, as well as ethnographic fieldwork, presenting a historical narrative of this issue from the time Buddhism enters Tibet up until modern times. The sale of statues, paintings of buddhas called thangkas, and texts is traditionally considered to be a sin, having severe negative karmic consequences. Before the Cultural Revolution (1966-76), Tibetans obtained their religious objects primarily through a process of commissioning an artist, and payment was made to the artist through voluntary offering with the patron (not the artist) setting the terms. However, today, the sale of such items as readymade objects is widespread within Tibetan areas of China. This book sheds light on why Tibetans are participating in such commercial practices today, going against long-accepted religious traditions and values. Catanese argues that while the commodification of religious goods has brought about financial rewards, social cohesion, the maintenance of artistic traditions, and has reaffirmed a sense of cultural and religious identity in Tibet, it has also significantly transformed the moral and ethical framework that accompanies the production and exchange of such objects, in the process also transforming Tibetan Buddhist identity"--